Wind Erosion and PM10 Emissions from No‐Tillage Cropping Systems in the Pacific Northwest. (1st July 2017) - Sharratt, Brenton; Young, Frank; Feng, Gary
Abstract : Core Ideas: Erosion of agricultural lands affect air quality in the Inland Pacific Northwest. Alternatives to tillage‐based cropping systems are needed to reduce wind erosion. No‐tillage cereal cropping systems reduce wind erosion and particulates ≤10 µm in diameter emissions. Economically viable strategies are sought for no‐tillage cropping systems. Wind erosion is a concern in the Inland Pacific Northwest (PNW) of the United States where the emission of particulates ≤10 µm in diameter (PM10) from winter wheat ( Triticum aestivum L.)/summer fallow (WW/SF) dryland cropping systems during high winds degrades air quality. There is a potential to reduce the risk of wind erosion using no‐tillage or chemical fallow cropping systems, but wind erosion observations are lacking from these systems. We measured sediment and PM10 flux from reduced‐tillage WW/SF, no‐tillage wheat/chemical fallow (NTW/CF), and no‐tillage spring barley ( Hordeum vulgare L.)/spring wheat (NTSB/SW) using a portable wind tunnel near Ralston, WA. Horizontal sediment flux, wind speed, and PM10 concentration were measured over two consecutive 10 min sampling periods inside the tunnel after sowing wheat in spring or late summer on four replications of the rotations. Sediment flux was measured with a modified Bagnold type sampler while wind speed and PM10 concentration were respectively measured with pitot tubes and aerosol monitors positioned at six heights above the soil surface inside the tunnel. Sediment and PM10 fluxes were an order of magnitude greater in late summer than spring. After sowing wheat in spring, sediment and PM10 fluxes were greater for the NTSB/SW than NTW/CF rotation while, after sowing winter wheat in late summer, sediment and PM10 fluxes were greater for the WW/SF than the NTSB/SW rotation. Our results suggest that wind erosion and PM10 emissions can be significantly reduced using no tillage cropping systems in the PNW.